UiTMLaw bracing the new normal 2020 - UiTM, Faculty of Law (Faculty of Law, 2020)
The Covid-19 pandemic has compelled schools, higher education institutions and training providers to go online to ensure that effective learning endures. While technology serves as the catalyst for a seamless migration of face-to-face learning to a virtual platform, access to quality digital content is pivotal, especially during the Movement Control Order (MCO) period. UiTMLaw, in thriving during this unprecedented time, established the Cl9-eLearn@UiTMLaw Task Force comprising the Dean, Assoc. Prof. Dr. Hartini Saripan, the Deputy Dean of Academic Affairs, Dr. Rafizah Abu Hassan, Prof. Dr. Irwin Ooi Ui Joo, Dr. Mohd Haris Abdul Rani, Mazlina Mohamad Mangsor, Mohd Yunus Abu Samah, Abdul Mu'iz Abdul Razak, Sarah Munirah Abdullah and Nurus Sakinatul Fikriah Mohd Shith Putera. The Task Force is charged with identifying areas of support necessary for the successful development, delivery and access to various Open and Distance Learning (ODL) approaches. In order to ensure smooth implementation of teaching and learning activities via such approaches, Guidelines to eLearning@UiTMLaw were produced, recommending well developed UiTM frameworks, tools, support facilities and infrastructure to handle both synchronous and asynchronous learning. Constant communication is maintained between the management, academic and administration staff, as well as students via UiTMLaw's landing page; UiTMLaw Standing Together, on top of the existing communication channels. The landing page is a one-stop information centre providing updates on the contingency plans for teaching and learning, including access to Guidelines to eLearning @UiTMLaw, Quick Guide to eLearning for Students and Lecturers, UiTMLaw Official Youtube Channel as well as eLearning platform tutorial videos and other recent information for student affairs and research activities. The Covid-19 pandemic is certainly an activator in moving the world towards the digital future- and UiTMLaw is ever ready to win this challenge triumphantly.